Raising recycling awareness through public art: using public art as a catalyst to rethink downtown Kansas City’s recycling system - Tudor, Harriett (Kansas State University, 2016)
Recycling programs and public art have the capacity to improve the urban environment and quality of life to enhance downtown neighborhoods for residents, employees, and visitors (Miles 1989; Kansas City Design Center 2015). Kansas City, Missouri, currently does not have a strategic recycling program in place for multi-family housing or commercial businesses. Additionally, Downtown lacks appropriate recycling infrastructure in the public realm. This lack of private and public recycling infrastructure has created a general lack of awareness within the Downtown community. Using public art as a catalyst, Downtown Kansas City has the opportunity to increase recycling participation and awareness in the public realm through an engaging recycling and public art system. This project will utilize the work from Kansas City Design Center (KCDC) spanning the Art in the Loop Vision Plan and the Recycling Vision Study. Through research and design development strategies, a cohesive system can build a network of connected sites that have strong relationships to both recycling and art narratives. These overlapping stories of recycling and art will activate the public realm driving increased awareness of the recycling issues. Collaboration with the KCDC studio and local artists has lead to the design implementation of the Showcase Node at the Main Street and Truman Road site which was established in the RE[CONSIDERED] vision proposal. This site will be activated through local artists each year and they will be challenged to utilize locally sourced recycled material to create artful and interactive installations. A temporary light frame structure will allow artist to house these rotating art installations to show the city what their recycled materials can transform into. Together, the coordination of public art and recycled materials can inspire and create a meaningful impact in Downtown Kansas City.
Keywords: Public Art; Recycling; Public Realm